ANALISA PENANGANAN SEDIMENTASI DENGAN SEPASANG JETTY PADA MUARA SUNGAI SERAYU - Iwan Rustendi; Rizka Riadianto; Novi Andhi Setyo Purwono; Fauzan Angga Musthafa (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2020)
The estuary functions as a discharge from the river, especially when it floods into the sea. The movement of currents from the sea and also the flow of water from upstream causes sedimentation problems in the estuary. Jetty building planning is required for handling sediment at the estuary of the Serayu River, which is planned with 35721 m2 construction area of a pair Wind data analysis for 10 years is carried out using software WRPLOT, AUTOCAD, and Google Earth. Concrete quality for making tetrapod using concrete (f’c) 31.2 MPa. The tetrapods used have a weight, width, height of 7.6 tons, 2.69 m, and 2.24 m, respectively. Geotextiles used in the jetty building design are 44781.68 m long. Security of the Serayu River estuary requires two pairs of the jetty, the jetty to the right of the estuary requires 778 m length and 34.6 m width, while the jetty to the left of the estuary requires 560 m length and 34.6 m width. The budget plan for the construction of a jetty for handling sediment at the estuary of the Serayu River is IDR 438,708,114,000.00.